Enhancing the building performance of low-cost schools in Pakistan - A study of natural ventilation, thermal comfort and moisture safety - ALATALO, ERIKA (My University, 2016)
This thesis studies how the building performance of low-cost charity schools in Pakistan could be improved. More specifically, the thesis studies the thermal comfort, natural ventilation and moisture safety of existing schools and aims to find ways to improve these with the help of passive techniques. Developing passive techniques is important because they mitigate climate change. In developing countries like Pakistan, passive techniques are also more easily accessible, because of the unreliable electricity supply and the cost of mechanical devices. The first step of the investigation was a field study to Pakistan where existing schools of The Citizens Foundation, a local educational non-profit organization, were visited in different parts of the country. During this field study traditional passive cooling techniques in Pakistan and Iran were also studied as a source of inspiration. The existing schools have then been studied with the help of a computational model developed in MATLAB and Simulink that calculates the free-running temperature and air change rate simultaneously. Alternative designs have then been tested with the same model to see which changes would be most beneficial. The focus has been on different natural ventilation strategies, but other factors such as building materials have also been studied. Thermal inertia, night ventilation, complementing regular windows with alternative openings, and reducing absorption of solar radiation with lighter surface colors have been identified as the most efficient passive design strategies. Pakistan has a variety of climates, and although the main problem in terms of thermal comfort is the heat of summer, winters in the north can be uncomfortably cold and this has also been identified as a problem during the thesis. These findings can be used as a basis when designing new schools. During the field study, mould growth and other moisture problems were also identified with the existing schools. The cause of these problems have been studied with the commercial software WUFI, but no definitive results have been obtained, and the problem would require further investigation.
Keywords: Materialvetenskap; Byggnadsteknik; Materials Science; Building engineering